Skua standing holding penguin foot - Olavarria, Carlos (School of Biological Sciences, University of Auckland, 2009)
In addition to the strong, hooked bill skuas share another characteristic with terrestrial birds of prey - the presence of hard scales, or scutes, on the legs, another indication of their predatory lifestyle.